2001
DOI: 10.1136/thorax.56.6.427
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells in the mucosa of the human trachea are not regularly found in the first year of life

Abstract: Background-Dendritic cells (DCs) in the mucosa of the respiratory tract might be involved in the early development of pulmonary allergy or tolerance. To date, little is known about when the first DCs occur in human airways. Methods-Specimens of the distal trachea from patients who had died from sudden death in the first year of life (n=29) and in older age groups (n=59) as well as from those who had died from respiratory tract infections in the first year of life (n=8) were examined by immunohistochemistry. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 34 publications
5
38
2
1
Order By: Relevance
“…Thus, whereas intraepithelial DC are rare in the intestinal tract, DC in the upper airway mucosae are preferentially located within the epithelial layer. Similar observations have previously been made in humans, rats and mice, with 400-800 of intraepithelial DC/ mm 2 of epithelial surface Tschernig et al 2001;Schon-Hegrad et al 1991). These cells actively participate in the generation of adaptive immune responses.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, whereas intraepithelial DC are rare in the intestinal tract, DC in the upper airway mucosae are preferentially located within the epithelial layer. Similar observations have previously been made in humans, rats and mice, with 400-800 of intraepithelial DC/ mm 2 of epithelial surface Tschernig et al 2001;Schon-Hegrad et al 1991). These cells actively participate in the generation of adaptive immune responses.…”
Section: Discussionsupporting
confidence: 80%
“…42 43 Influence of age We have previously reported that the density of DC, determined by HLA-DR staining and morphology in paraffin sections, is different in infants under the age of 1 year than in older individuals. 18 This is similar to data in the rat trachea in which the density of DC reached adult levels 2 weeks after birth. 44 In the present study the patients were also divided into two age groups (younger or older than 1 year of age), and age dependent differences were found at certain topographical sites.…”
Section: Expression Of Markers and Correlationsupporting
confidence: 88%
“…29 In a previous study with paraffin embedded tissues, the presence of DC in the human trachea was examined using HLA-DR labelling and morphology because of a lack of antibodies staining paraffin sections. 18 In a recent study DC were characterised, in addition to other leucocytes, in situ in frozen human post mortem tissue and resection material. In this investigation no differences in the cell numbers were found between post mortem and surgical samples.…”
mentioning
confidence: 99%
“…This is supported by reports showing differences in the absolute numbers of blood DC subsets in young children compared to older children and adults (11,31). Similar reductions in DC numbers within mucosal tissue in early life have also been reported (23,34). Over and above the low numbers of blood DC at 12 months, it is likely that there are additional deficits in APC function at this age.…”
supporting
confidence: 72%